A symptomatic cystic axillary mass in a post-partum female. Issue 2 (14th February 2023) - Werwie, Nicole; Oostra, Jodi; Hanley, Kelly
Abstract: Hemangiomas are rarely found in the axilla, with the most commonly identified axillary mass being lymphadenopathy. We report a unique case report of a post-partum female with an axillary mass that became larger and symptomatic while breastfeeding. On imaging, the mass was found to be complex and cystic, and aspiration was attempted several times. With a rapid return of swelling and worsening symptoms, there was concern for bleeding into the cystic cavity. Ultimately, the >10 cm mass had to be formally excised in the operating room, yielding definitive relief of symptoms. Final pathology reported the mass as a vascular malformation, either a hemangioma or arteriovenous malformation. It has been postulated that estrogen and progesterone may stimulate the growth of hemangiomas, which may explain this patient's post-partum presentation. This case demonstrates a perplexing axillary mass that continued to re-accumulate until final excision.